Implantation of a Sapien XT Aortic Bioprosthesis through the Left Carotid Artery. Issue 3 (12th January 2014) - Modine, Thomas; Sudre, Arnaud; Amr, Gilles; Delhaye, Cedric; Koussa, Mohamad
Abstract Transcatheter aortic valve implantation (TAVI) is still under active investigation. When the femoral route is impossible for anatomic reasons, the transapical, transaxillary and direct aortic approaches have demonstrated their effectiveness. We report the successful implantation of a Sapien XT bioprosthesis with the NovaFlex catheter through a left carotid approach. doi: 10.1111/jocs.12289 (J Card Surg 2014;29:337–339)